Drivers of real interest rates in a two-country, general-equilibrium, OLG model - Frederik Bjørn Christensen; Jesper Pedersen (Danmarks Nationalbank, 2023)
What can explain the long-term decline in equilibrium real interest rates? We analyze the importance of three of the most cited drivers; decreasing fertility, decreasing mortality, and a slowdown of technological growth. We do this through the lens of a general-equilibrium, two-country, overlapping generations model with international capital markets and trade in goods. Using the US as a proxy for the world economy, we find that all three factors put downward pressure on the global real interest rate. The model predicts a 2.25 percentage point decrease from 1950 until today with falling mortality generating most of the decline. We calibrate the second country on Danish data and show how differences in mortality can help explain the build-up of the large Danish net foreign asset position. Our results suggest that the secular decline in real interest rates is not fully over; the drivers considered in this analysis are likely to depress real interest rates by another 0.25 percentage points going forward from today until 2050
Keywords: E21; E22; E37; E43; E47; 330; Real Interest Rates; Mortality; Fertility; Technology; Trade; International Capital Markets